Osteochondritis Dissecans of the Knee Joint (Osgood-Schlatters Disease) (Journal of Experimental and Clinical Anatomy, 2005)
An 18-year-old male professional footballer presented in the surgical outpatient department (SOP) of University of Nigeria Teaching Hospital Enugu complaining of bilateral knee-joint pains and tenderness severe enough to prevent him from participating in training sessions and professional league matches. Both knee joint were X-rayed and the radiographs revealed bilateral Osteochondritis dissecans of the knee joints (Osgood schlatters disease). This case is being reported to highlight on the epidemiology, etiology clinical appearance, possibilities for radiological diagnoses, classification of ostechondritis dissecans, the various treatment modalities available complications of osteochondritis dissecans and above all emphasizes on the benignity of the disease.